Intra- and inter-model reliability of Hemocue Hb 201+ and HemoCue Hb 301 devices - Ashish Jain; Nilotpal Chowdhury; Sanchit Jain (Asian Journal of Transfusion Science, 2018)
Aim: The study intended to estimate the intra- and inter-model reliability and agreement between the HemoCue Models 201+ and 301 in a blood bank donor screening setting. Materials and Methods: Venous blood samples from 115 blood donors were analyzed by two Hemocue 201+ instruments and two HemoCue 301 instruments. The Lin's concordance correlation coefficient (CCC) as well as the Bland–Altman limits of agreement was measured. Results: The 95% lower confidence interval (CI) of all the CCCs had a value >0.90. The CCC between instruments belonging to the same model was compared to instruments belonging to different models. The mean of HemoCue 301 was higher than HemoCue 201+ by 3.04 g/L with the 95% CI of the differences (i.e., the limits of agreement) between the two models ranging from −3.35 to 9.44 g/L. The bias between two instruments was lesser, and the limits of agreement were even narrower between instruments belonging to the same model. Conclusion: The inter-instrument reliability and agreement are satisfactory in a blood bank setting.